Systematic Literature Review (SLR): The Effectiveness of Learning Models in Improving Students' Scientific Argumentation Skills in Chemistry Learning - Juliana Zahwa; Najwa Fitri Desaspriya; Miterianifa Miterianifa (Jurnal Pendidikan dan Pembelajaran Kimia, 2026)
Systematic Literature Review (SLR): The Effectiveness of Learning Models in Improving Students' Scientific Argumentation Skills in Chemistry Learning. Scientific argumentation skills are an important component in chemistry learning that involves reasoning based on evidence, interpretation of experimental data, and science-based decision making. Therefore, this study aims to review the effectiveness of various learning models on student skills using the Systematic Literature Review method using the Google Scholar database, with the PRISMA framework. After an initial search, 5.510 articles were found. However, after going through the identification, screening, eligibility, and inclusion processes in this study, only articles published between 2020 and 2025 that were relevant to high school chemistry material were included. Thus, only 14 articles met the inclusion criteria. The SLR results showed that the scientific argumentation learning model through the Argument-Driven Inquiry approach was the most effective, demonstrating an increase in the quality of scientific arguments, critical thinking, and problem-solving skills of students in the subjects of acids and bases, buffer solutions, chemical equilibrium, and reaction rates. Cooperative ADI also provides a significant difference in improving students' argumentation skills compared to conventional inquiry. In addition, Inquiry and Guided Inquiry have been proven effective in improving students' chemistry literacy, Nature of Science, and scientific attitudes in electrolyte, stoichiometry, and redox materials. The conclusions of this SLR prove that the two inquiry and argumentation learning models make a positive contribution to the abstract relationship between chemistry material and student reasoning. Therefore, these findings are expected to form the basis for a pedagogical approach to chemistry education in order to sharpen students' scientific argumentation skills.